2011
DOI: 10.1111/j.1526-100x.2011.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Ants as Indicators of the Success of Rehabilitation Efforts in Deposits of Gold Mining Tailings

Abstract: The evaluation of the success of restoration efforts is an essential step for environmental monitoring programs, providing reliable and intricate information on the response of biotic and abiotic elements of ecosystem following the restoration programs adopted. The aim of this study was to evaluate the efficacy of different rehabilitation efforts after gold mining activities using ants as bioindicators. We tested the following hypotheses: (1) the ant species richness and composition vary with the technique of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
2
13
0
15
Order By: Relevance
“…Management systems with homogeneous vegetation do not attract native fauna organisms as much as systems with forest species (Ribas et al, 2011). Silva et al, (2009) investigated the effects of soil management systems on the soil invertebrate community of a secondary forest and manioc monoculture and reported that richness was lower in the manioc culture, particularly in the dry season.…”
Section: Abundance Composition and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Management systems with homogeneous vegetation do not attract native fauna organisms as much as systems with forest species (Ribas et al, 2011). Silva et al, (2009) investigated the effects of soil management systems on the soil invertebrate community of a secondary forest and manioc monoculture and reported that richness was lower in the manioc culture, particularly in the dry season.…”
Section: Abundance Composition and Diversitymentioning
confidence: 99%
“…Variations in the vegetation composition and in soil management, litter quality, food availability, and degree of degradation or recovery of the ecosystem have a great influence on the soil invertebrate community (Moço et al, 2005;Baretta et al, 2006;Silva et al, 2006;Dias et al, 2007;Azevedo et al, 2008;Ribas et al, 2011). In general, the removal of the vegetation results in a simpler habitat, which immediately reduces food supply and diversity, and shelter and reproduction sites (Guerra et al, 1982;Souto et al, 2008;Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The poneromorph ants have a great ecological importance, occupying different trophic levels (Brandão et al, 2011), thus participating in mutualistic plant associations (Pereira et al, 2013), facilitating seed dispersal (Leal et al, 2014). This group of insect also plays a prominent role inbioindicators of anthropic impacts such as the use of pastures (Dias et al, 2008), fires (Endanger et al, 2008), and mining (Ribas et al, 2012).…”
mentioning
confidence: 99%
“…Raup-Crick was used because it is a robust index that calculates how different pairwise samples are than expected by chance implementing null models which consider the variation in the number of local species and alpha diversity (Chase et al, 2011). This index is frequently used to compare the dissimilarity of invertebrate communities between different habitats (RyderWilkie et al, 2010;Ribas et al, 2012;Reis et al, 2013). We utilized the first two PCoA axis (which represented 66.76 % of explication) in a Multivariate Analysis of Variance (MANOVA) as dependent variables and vertical habitat (ground and understory) as a factor.…”
Section: Discussionmentioning
confidence: 99%